PENDUDUK DAN PENGANGGURAN: SEBUAH ANALISIS KEPENDUDUKAN DI PROVINSI JAWA TIMUR - Sayekti Suindyah (Fakultas Ekonomi Universitas Darul Ulum, 2014)
The purpose of this study is to analyze and prove the existence of influence between the rate of population growth with the open unemployment in the province of East Java with his time of September until December 2011. The source of the data used in this study is secondary data coming from the Bappeda of East Java and East Java BPS. The method of data collection is done in this research is the study of librarianship or documentation, with the study of time series of research using data based on the time sequence. Statistical tests used was a simple linear regression analysis and regression natural logarithm with the help of the program SPSS 11.5 for windows. Research results mnyimpulkan that: 1. the negative impact of population growth on the open unemployment in East Java. 2. the rate of population growth has a positive influence on the numbers TPAK in East Java. 3. the rate of population growth in line with the demand for labor in East Java. 4. Population growth affect PMA. 5. Calculation result shows that if population growth is growing. 6. Population density affect negatively to economic growth. 7. Calculation of Results the analysis stated that there were negative influences between economic growth with open unemployment.